2019
DOI: 10.3390/ani9050226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Protein Diets and Exogenous Protease on Growth Performance, Carcass Traits, Intestinal Morphology, Cecal Volatile Fatty Acids and Serum Parameters in Broilers

Abstract: Dietary exogenous proteases (ENZ) can be used in poultry production to improve the growth of chickens fed low-protein (LP) diets. We hypothesized that ENZ supplemented in an LP diet would improve growth performance and physiological response in broilers for 8–35 days. To investigate this, we used a 2 × 2 factorial design with crude protein (CP, normal diet (NP) and LP) and ENZ. The LP diet contained low in 1% CP and ca. 8–12% amino acids compared to the NP diet and both NP and LP diets were added without or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 55 publications
8
35
0
Order By: Relevance
“…while albumin level in the plasma was elevated by supplement graded levels of protease 100, 200, and 300 mg/kg. It has been showed that the concentration of plasma albumin related to improving the immunity status in birds (Laborde et al 1995;Ding et al 2016;Saleh 2017;Ndazigaruye et al 2019). Our results are in harmony with Allouche et al (2015) who found that plasma protein concentrations were enhanced by dietary protease supplementations.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…while albumin level in the plasma was elevated by supplement graded levels of protease 100, 200, and 300 mg/kg. It has been showed that the concentration of plasma albumin related to improving the immunity status in birds (Laborde et al 1995;Ding et al 2016;Saleh 2017;Ndazigaruye et al 2019). Our results are in harmony with Allouche et al (2015) who found that plasma protein concentrations were enhanced by dietary protease supplementations.…”
Section: Discussionsupporting
confidence: 86%
“…Increasing the supplemental protease levels were associated with decreasing the plasma levels of CHO, GLU, TG, and LDL-cholesterol and elevated HDL-cholesterol level in the current study. However, in another recent study (Ndazigaruye et al 2019) it has been reported that serum total protein, albumin, TG, CHO, creatinine, HDL-cholesterol, GOT, and GPT levels did not change in broiler fed diets with protease. The disagreement between our data and their data may be due to some factors such as the nutrient composition of the diets (sufficient/insufficient protein), enzyme used (source of enzymes, doses), and raw protein sources used which could alter some conditions of the digestive tract such as the pH.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Malondialdehyde ( MDA ) was measured using the OxiSelect TBARS Assay kit (Cell Biolabs, Inc., San Diego, CA). Nitric oxide in serum samples was determined as described by Ndazigaruye et al. (2019) using the Griess reagent (Sigma-Aldrich, St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…The higher level of ALB could also be associated with synthetic amino acid supplementation in the diet [28]. UA concentrations are the indicator of amino acid utilization in chickens fed amino acid-deficient diets [29] and CRE is a product of creatine phosphate in muscle tissue, and its production is proportional to muscle mass [30]. The higher glucose level by a reduced protein diet could be because of the increased intake of nutrients and decrease insulin sensitivity affecting the transport and utilization of GLU [31].…”
Section: Nitrogen Digestibilitymentioning
confidence: 99%